The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1111/j.1365-2273.1994.tb01194.x
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck carcinoma ? stage at presentation

Abstract: A prospective study was performed during a 2-year-period. A total of 127 patients presenting with a squamous cell carcinoma of the head, neck and upper aerodigestive tract were entered into the study. Patients were classified according to the primary site, namely: larynx (n = 44), oropharynx (n = 28), hypopharynx (n = 17) and oral cavity (n = 19) and others (n = 19). Patients were staged according to the UICC TNM classification (1987) and the nature and duration of their symptoms were recorded. Sixty-one per c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
1
4

Year Published

1995
1995
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 22 publications
3
28
1
4
Order By: Relevance
“…The final fully adjusted model shows how delay in diagnosis negatively affects prognosis, by increasing both recurrence and oral cancer mortality rates. Several previous studies report on the importance of early diagnosis in the prognosis of oral cancer patients 8,15,21 . Other studies have reported no association between diagnosis delay and oral cancer survival 8,15 .…”
Section: Diagnostic Delaymentioning
confidence: 99%
“…The final fully adjusted model shows how delay in diagnosis negatively affects prognosis, by increasing both recurrence and oral cancer mortality rates. Several previous studies report on the importance of early diagnosis in the prognosis of oral cancer patients 8,15,21 . Other studies have reported no association between diagnosis delay and oral cancer survival 8,15 .…”
Section: Diagnostic Delaymentioning
confidence: 99%
“…More than 60% of head and neck squamous cell carcinoma (HNSCC) patients present with advanced-staged disease, which is associated with a high mortality rate [1]. The current treatment for advanced-stage HNSCC is cisplatin and radiation for patients with good performance status; patients with limited performance status receive high-dose cisplatin alone [2][4].…”
Section: Introductionmentioning
confidence: 99%
“…About one third of the patients present with early-stage disease (stages I and II; see Table 1), whereas two thirds of the patients present with advanced-stage disease (stages III and IV; ref. 2). Initial therapy of HNSCC is surgery and/or radiotherapy.…”
Section: Introductionmentioning
confidence: 99%